The motion of imagery and the construction of meaning in television drama-An analytical study - Kamal Shanawi Dheyab (Peerian Journals Publishing, 2024)
Movement has constituted a fundamental element of allure and suspense in cinema, showcasing its capacities in attraction, maneuvering, and variation within the frame and motion itself, both cinematically and on television. Movement has fulfilled a multitude of functions and expressions, often imbuing the dramatic scene with significance and meaning for the audience. This phenomenon has compelled numerous filmmakers in cinema, theatre, and television to rigorously design movement. The visual arts, particularly painting, have concentrated on this aspect, generating movement within the frame to construct meaning and significance that realize the artist's creative intent. Given its importance, this study examines the role of movement, structure, and meaning, and their manifestation in television drama.
Keywords: Movement; Image; Structure